1985
DOI: 10.1128/jb.161.1.85-90.1985
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis and cloning analysis of the pathways for degradation of 2,4-dichlorophenoxyacetic acid and 3-chlorobenzoate in Alcaligenes eutrophus JMP134(pJP4)

Abstract: Plasmid pJP4 permits its host bacterium, strain JMP134, to degrade and utilize as sole sources of carbon and energy 3-chlorobenzoate and 2,4-dichlorophenoxyacetic acid (R. H. Don and J. M. Pemberton, J. Bacteriol. 145:681-686, 1981). Mutagenesis of pJP4 by transposons TnS and Tnl 771 enabled localization of five genes for enzymes involved in these catabolic pathways. Four of the genes, tfdB, tfdC, tfdD, and tfdE, encoded 2,4-dichlorophenol hydroxylase, dichlorocatechol 1,2-dioxygenase, chloromuconate cycloisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(96 citation statements)
references
References 17 publications
1
95
0
Order By: Relevance
“…This work clearly demonstrated that no additional tfd genes or pseudogenes are encoded in pJP4. The sequence of the tfd genes in pJP4 perfectly matched that reported previously (Don et al, 1985;Laemmli et al, 2000). However, an additional G in the position 1020 of the tfdD II gene (ORF 29) produces a protein of 372 aa, which is 23 residues larger than that described previously (Laemmli et al, 2000), but of a size very similar to other reported chloromuconate cycloisomerases.…”
Section: Additional Catabolic Functions In Pjp4supporting
confidence: 82%
“…This work clearly demonstrated that no additional tfd genes or pseudogenes are encoded in pJP4. The sequence of the tfd genes in pJP4 perfectly matched that reported previously (Don et al, 1985;Laemmli et al, 2000). However, an additional G in the position 1020 of the tfdD II gene (ORF 29) produces a protein of 372 aa, which is 23 residues larger than that described previously (Laemmli et al, 2000), but of a size very similar to other reported chloromuconate cycloisomerases.…”
Section: Additional Catabolic Functions In Pjp4supporting
confidence: 82%
“…The plasmids pJP4 and pAC25 have been extensively characterized and show significant ho-mology, suggesting that they have a common ancestral origin [371,372]. The genes for chlorocatechol degradation (pyrocatechase, cycloisomerase, hydrolase, lactone isomerase) are clustered as one operon [373,374]. The complete nucleotide sequences of chlorocatechol oxidative operons have been determined [374,375].…”
Section: Genetic Basis Of Degradation and Construction Of Novel Strainsmentioning
confidence: 99%
“…d PCR results show that these strains contain two dehalogenases, both a group I deh (D,L-2MCPA-speci¢c) and a group II deh (L-2MCPA-speci¢c). e Exogenously isolated plasmid pQKH90 carrying strain of R. eutropha JMP222 [24]. UWC11 is isogenic to UWC10.…”
Section: Isolation and Characterisation Of Deh Genes From Soil Enrichmentioning
confidence: 99%